2019
DOI: 10.15698/mic2019.09.690
|View full text |Cite
|
Sign up to set email alerts
|

Diverse conditions support near-zero growth in yeast: Implications for the study of cell lifespan

Abstract: Baker's yeast has a finite lifespan and ages in two ways: a mother cell can only divide so many times (its replicative lifespan), and a non-dividing cell can only live so long (its chronological lifespan). Wild and laboratory yeast strains exhibit natural variation for each type of lifespan, and the genetic basis for this variation has been generalized to other eukaryotes, including metazoans. To date, yeast chronological lifespan has chiefly been studied in relation to the rate and mode of functional decline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 155 publications
(211 reference statements)
0
8
0
Order By: Relevance
“…With respect to the industrial application of the zero‐growth concept, the use of membrane filters to achieve cell retention might be less feasible on an industrial scale, as blocking of effluent filters could prevent long‐time operation. Alternative means of cell retention could involve the use of fast‐sedimenting yeast mutants (Oud et al, 2013) or cell immobilization (Gulli et al, 2019; Nagarajan et al, 2014). Near‐zero growth conditions can also be achieved by controlling the feed of a limiting nutrient in fed‐batch processes.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the industrial application of the zero‐growth concept, the use of membrane filters to achieve cell retention might be less feasible on an industrial scale, as blocking of effluent filters could prevent long‐time operation. Alternative means of cell retention could involve the use of fast‐sedimenting yeast mutants (Oud et al, 2013) or cell immobilization (Gulli et al, 2019; Nagarajan et al, 2014). Near‐zero growth conditions can also be achieved by controlling the feed of a limiting nutrient in fed‐batch processes.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 6, 2022. ; https://doi.org/10.1101/2022.09.06.506712 doi: bioRxiv preprint Retentostat studies have shown the importance of this system in elucidating the mechanisms involved in survival of microbial cells in environments with extremely low nutrient availability (4,10,(12)(13)(14)(15)(16)(17). In these conditions, microbial cells use different strategies to adapt to the nutritional stress in order to survive.…”
Section: Introductionmentioning
confidence: 99%
“…Retentostat studies have shown the importance of this system in elucidating the mechanisms involved in survival of microbial cells in environments with extremely low nutrient availability (4,10,(12)(13)(14)(15)(16)(17). In these conditions, microbial cells use different strategies to adapt to the nutritional stress in order to survive.…”
Section: Introductionmentioning
confidence: 99%
“…Use of membrane filters to achieve cell retention might be less feasible on an industrial scale as blocking of effluent filters could prevent long-time operation. Alternative means of cell retention could involve use of fastsedimenting yeast mutants (Oud et al, 2013) or immobilization (Gulli et al, 2019;Nagarajan et al, 2014) might be explored. Near zero growth conditions can also be achieved by controlling the feed of a limiting nutrient in fed-batch processes.…”
Section: Discussionmentioning
confidence: 99%